Suppression of intrahepatic cholangiocarcinoma cell growth by SKI via upregulation of the CDK inhibitor p21. Issue 12 (26th September 2022) - Kawamura, Etsushi; Matsubara, Tsutomu; Daikoku, Atsuko; Deguchi, Sanae; Kinoshita, Masahiko; Yuasa, Hideto; Urushima, Hayato; Odagiri, Naoshi; Motoyama, Hiroyuki; Kotani, Kohei; Kozuka, Ritsuzo; Hagihara, Atsushi; et al.
Abstract : Cholangiocarcinoma (CC) has a poor prognosis and different driver genes depending on the site of onset. Intrahepatic CC is the second‐most common liver cancer after hepatocellular carcinoma, and novel therapeutic targets are urgently needed. The present study was conducted to identify novel therapeutic targets by exploring differentially regulated genes in human CC. MicroRNA (miRNA) and mRNA microarrays were performed using tissue and serum samples obtained from 24 surgically resected hepatobiliary tumor cases, including 10 CC cases. We conducted principal component analysis to identify differentially expressed miRNA, leading to the identification of miRNA‐3648 as a differentially expressed miRNA. We used an in silico screening approach to identify its target mRNA, the tumor suppressor Sloan Kettering Institute ( SKI ). SKI protein expression was decreased in human CC cells overexpressing miRNA‐3648, endogenous SKI protein expression was decreased in human CC tumor tissues, and endogenous SKI mRNA expression was suppressed in human CC cells characterized by rapid growth. SKI‐overexpressing OZ cells (human intrahepatic CC cells) showed upregulation of cyclin‐dependent kinase inhibitor p21 mRNA and protein expression and suppressed cell proliferation. Nuclear expression of CDT1 (chromatin licensing and DNA replication factor 1), which is required for the G1/S transition, was suppressed in SKI‐overexpressing OZ cells. SKI knockdown resulted in the opposite effects. Transgenic p21‐luciferase was activated in SKI‐overexpressing OZ cells. These data indicate SKI involvement in p21 transcription and that SKI–p21 signaling causes cell cycle arrest in G1, suppressing intrahepatic CC cell growth. Therefore, SKI may be a potential therapeutic target for intrahepatic CC. Abstract : We analyzed clinical intrahepatic cholangiocarcinoma (CC) samples, focusing on the microRNA‐3648 and its target mRNA, the tumor suppressor Sloan Kettering Institute (SKI). We found that SKI was involved in the transcription of the cyclin‐dependent kinase inhibitor p21. SKI–p21 signaling may act as a brake, preventing cell cycle progression in G1 phase, resulting in the suppression of CC cell growth.